Pengaruh DPR, ROA Dan Inflasi Terhadap Volatilitas Harga Saham - Ratu Andhita Trihadiyanti; Immas Nurhayati; Renea Shinta Aminda (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the simultaneous and partial effect of the Dividend Payout Ratio, Return On Assets and Inflation on Stock Price Volatility in Property, Real Estate, And Building Construction sector companies listed on the Jakarta Islamic Index (JII) for the 2012-2021 period. The objects of this research are all property, real estate, and building construction companies listed on the Jakarta Islamic Index (JII) for the 2012-2021 period. The sampling method used purposive sampling with a total of 5 companies in the Property, Real Estate and Building Construction sector. The data analysis method used is the classical assumption test, panel data regression analysis, analysis of the correlation coefficient and determination, hypothesis testing using the t test (partial) and f test (simultaneous). The results using the t (partial) test show that the Dividend Payout Ratio variable has a significant effect on Stock Price Volatility, while the Return On Assets and Inflation variables have no significant effect on Stock Price Volatility. Then the f (simultaneous) test shows that the variables Dividend Payout Ratio, Return On Assets and Inflation have a significant effect on stock price volatility.